The Road to Omaha - Ludlum, Robert (New York Random House Inc, 1992)
"The flames roared up in the night sky, creatimh massive shadows pulsating across the painted faces of Indians around the bonfire. And than, the chief of the tribe, bedecked in the ceremonial garments of his office, his feathured headdress swooping down from his immencely tall frame to the ground below, raised his voice in regal majesty..."
Keywords: Fiction